2003
DOI: 10.4315/0362-028x-66.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Filament Formation by Salmonella spp. Inoculated into Liquid Food Matrices at Refrigeration Temperatures, and Growth Patterns When Warmed

Abstract: In this study, the formation of multicellular filamentous Salmonella cells in response to low temperatures was investigated by using isolates of Salmonella enterica serovar Enteritidis PT4 and S. enterica serovar Typhimurium DT104 as the inocula. The formation of filamentous cells in two liquid food matrices at the recommended maximum temperature for refrigeration (8 degrees C) was monitored and compared with that in tryptone soya broth. Giemsa staining was performed to locate nuclear material within the filam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…They found that filament formation with increased filament length became apparent in 5% sodium chloride and 7% potassium chloride (Zarei et al, 2012). These findings were also observed in Salmonella at low water activity and low temperature (Mattick et al, 2000(Mattick et al, , 2003.…”
Section: Resistance To Bacteriocinssupporting
confidence: 65%
“…They found that filament formation with increased filament length became apparent in 5% sodium chloride and 7% potassium chloride (Zarei et al, 2012). These findings were also observed in Salmonella at low water activity and low temperature (Mattick et al, 2000(Mattick et al, , 2003.…”
Section: Resistance To Bacteriocinssupporting
confidence: 65%
“…Different serovars of S. enterica filament during growth in hyperosmotic, acidic, alkali, and refrigerated environments (19,31,(34)(35)(36). Likewise, both E. coli and L. monocytogenes filament in similar suboptimal conditions (19,29,36,61).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reduced-a w conditions, exposures to low or elevated temperatures and acid or alkaline pH levels lead to filament formation by Salmonella (19,24,25). Regardless, it appears to be a conserved response in several food-borne pathogens, including Listeria monocytogenes (1,9,16,17), E. coli O157:H7 (25), and Bacillus cereus (21).…”
Section: Discussionmentioning
confidence: 99%
“…Filamentous cells remained as filaments at both temperatures. We extended the incubation at 4°C to 19 days to determine whether prolonged cold stress would induce filamentation by the E40 control cells, as was observed by Mattick et al (24). No filamentation was observed.…”
Section: Fig 2 Morphology Of Smentioning
confidence: 99%
See 1 more Smart Citation